THE BEST TIME TO SELL WHEAT. POLAND AS A CASE STUDY - Grzegorz Przekota; Szczepańska-Przekota, Anna (Management and Administration Journal, 2020)
Seasonality is a typical phenomenon for agricultural markets, but its scale may be different for individual products. Climatic conditions cause differences in the supply of commodities throughout the year, and this generates price volatility. The aim of the study is to assess the distribution of seasonal fluctuations in wheat prices in Poland in the years 2000-2020 and to determine the optimal moment for selling wheat from the agricultural producer’s point of view. The price distribution analysis also took into account the cost of storage. The analysis was based on descriptive statistics and confidence intervals for mean values. The conducted research made it possible to evaluate the price distribution over the following seasons. It’s difficult to clearly indicate the most favorable months for selling wheat. There are many indications that it may be January. However, market conditions are so volatile that the situation may change unexpectedly throughout the year.